Effects of binders on the properties of bio-char pellets. (1st November 2015) - Hu, Qiang; Shao, Jingai; Yang, Haiping; Yao, Dingding; Wang, Xianhua; Chen, Hanping
Highlights: Bio-char was densified with four binders of varying content (5–20%). The rheological characteristics of pellets were analyzed. Starch pellets showed good hydrophobicity, but low volume density and poor mechanical strength. NaOH pellets showed highest compressive strength and hydroscopicity among all pellets. Lignin and Ca(OH)2 pellets exhibited more desirable characteristics for use as biofuels. Abstract: Bio-char, produced from biomass pyrolysis, can be pelletized to improve its undesirable characteristics, such as low bulk and energy densities, poor transportation and storage properties, and troublesome to co-fire with coal. In this study, rice husk char was compressed into pellets with four kinds of binders (lignin, starch, calcium hydroxide and sodium hydroxide). The compressive process, mechanical strength, basic fuel properties, and combustion characteristics were investigated to elucidate the effect of binders on the properties of bio-char pellets. Results showed that starch pellets had good hydrophobicity, but low volume density and poor mechanical strength. The softening and morphological transition of lignin during compression may account for the high elastic modulus and good bonding of lignin pellets. The low saturated moisture content of Ca(OH)2 pellets is mainly ascribed to its hydration. NaOH pellets showed the highest compressive strength among all pellets, and also exhibited the highest moisture uptake that may worsen the handling and storage treatment of bio-char. Compared with raw bio-char, bio-char pellets had a lower ignition temperature, wider temperature interval, and higher oxidation activity according to the thermogravimetric analysis. The lignin and Ca(OH)2 pellets showed lower compression energy consumption and moisture uptake, enhanced mechanical strength and promoted combustion performance, which demonstrated more desirable properties for utilization as biofuels.